Pembuatan Deterjen Sintetic Cair Pembersih Tangan - Budi Utami (Balai Besar Kimia dan Kemasan, 1995)
The experiment of liquid toilet deterjen has been done in a laboratoryscale by using five different formulations. Each formulation was tested according to the SNI 06 - 2588 - 1992.The formulation which is comply with the SNI requirement and has the lowes cost can be seen in table 2, formulation V which has pH = 6,5630 and active ingredients 7,33 %.